Stripping Voltammetric Determination of Lead in Coastal Waters With a Functional Micro-Needle Electrode - Han, Haitao; Pan, Dawei; Li, Ying; Wang, Jie; Wang, Chenchen (Frontiers in Marine Science, 2020)
In this work, for the voltammetric determination of lead (Pb) in coastal waters, a novel functional micro-needle electrode based on 3D reduced graphene oxide/flower-like bismuth nanosheets (3DrGO/F-BiNSs) was fabricated. The micro-needle electrode was prepared with the commercial acupuncture needle (ANE) and functionalized with 3DrGO/F-BiNSs through stepwise electrodeposition method. The sensing surface (needle tip) of the micro-needle electrode was first modified with 3DrGO to enhance the conductivity and provide more active sites to combine Bi nanomaterials. Then the F-BiNSs were electrodeposited on the 3DrGO surface to facilitate the electrochemical voltammetric response of Pb2+ due to their excellent combining ability with Pb. The physical and electrochemical properties of the as-prepared 3DrGO/F-BiNSs/ANE were characterized by different techniques including scanning electron microscope (SEM), energy dispersive X-ray spectroscopy (EDS), and electrochemical methods. The 3DrGO/F-BiNSs/ANE exhibited an excellent performance for the voltammetric determination of Pb2+ with the linear range of 40 to 600 nmol L-1 and detection limit of 12.5 nmol L-1. Additionally, the application of the functional micro-needle electrode for Pb determination in different coastal water samples was also investigated.